Remote Sensing Reveals Multi-Dimensional Functional Changes in Fish Assemblages Under Eutrophication and Hydrological Stress - Anastasiia Zymaroieva; Dmytro Bondarev; Olga Kunakh; Jens-Christian Svenning; Oleksander Zhukov (Fishes)
Understanding how fish communities respond to long-term environmental changes in regulated floodplain ecosystems is essential for managing biodiversity amid increasing anthropogenic and climatic pressures. This study evaluates the spatiotemporal dynamics of functional diversity in juvenile fish assemblages within the Dnipro-Orilskiy Nature Reserve (Ukraine) from 1997 to 2015. By employing a combination of extensive ichthyological field surveys and satellite-derived environmental indices (including NDVI, chlorophyll-a, turbidity, and spectral proxies for algal blooms), we assessed the impacts of eutrophication, hydrological alterations, and climate warming on functional structure. Our results reveal three key responses in fish functional diversity: (1) a decline in functional specialization and imbalance, indicating the loss of unique ecological roles and increased redundancy; (2) a rise in functional divergence, reflecting a shift toward species with outlying trait combinations; and (3) a complex pattern in functional richness, with trends varying by site and trait structure. These shifts are linked to increasing eutrophication and warming, particularly in floodplain areas. Remote sensing effectively captured spatial variation in eutrophication-related water quality and proved to be a powerful tool for linking environmental change to fish community dynamics, not least in inaccessible areas.